VARIANTS FOR EVALUATING THE RIGIDITY OF FLAT RING FLANGES - RADU I. IATAN; GHEORGHITA TOMESCU; MELANIA CORLECIUC (MITUCA); GEORGETA ROMAN (URSE); NICOLETA SPOREA; IULIANA- MARLENA PRODEA; IOLANDA CONSTANTA PANAIT (Journal of Engineering Studies and Research)
This paper describes an analytical way of comparative evaluation of the stiffnesses developed in assemblies with flat ring flanges, of optional type, welded to the cylindrical body of a pressure vessel. Based on the theory of the compatibility of deformations (radial displacements and rotations), the mathematical expressions necessary for the evaluation of the unitary radial bending moments and the unitary shearing forces of connection are established. With their help, the values of the rotation angles of the rings can be calculated and compared with the admissible ones. The present analysis considers the quantitative effect of the deformed gasket and the stiffness of the curved/bent screws on the tightness of the system. The methodology is flexible by introducing some selection factors, so that the mentioned influences can be easily separated and compared.